2019
DOI: 10.1007/s12649-019-00649-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomethanation of Syngas by Enriched Mixed Anaerobic Consortia in Trickle Bed Reactors

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Biomethanation of syngas has also recently been demonstrated an effective syngas-to-methane technology on the lab scale and shows potential for scale-up [28]. In a previous techno-economic assessment on an integrated biomass gasification-electrolysis-biomethanation (IBGEB) process, we identified a bSNG minimum selling price of 2.68 €/Nm 3 and we indicated that key optimization opportunities rely on lower-pressure operation and better energy integration within the process [11].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Biomethanation of syngas has also recently been demonstrated an effective syngas-to-methane technology on the lab scale and shows potential for scale-up [28]. In a previous techno-economic assessment on an integrated biomass gasification-electrolysis-biomethanation (IBGEB) process, we identified a bSNG minimum selling price of 2.68 €/Nm 3 and we indicated that key optimization opportunities rely on lower-pressure operation and better energy integration within the process [11].…”
Section: Introductionmentioning
confidence: 78%
“…In a previous techno-economic assessment on an integrated biomass gasification-electrolysis-biomethanation (IBGEB) process, we identified a bSNG minimum selling price of 2.68 €/Nm 3 and we indicated that key optimization opportunities rely on lower-pressure operation and better energy integration within the process [11]. As an important advantage over catalytic methanation, syngas biomethanation offers the possibility of low-pressure [22,23] or atmosphericpressure [28] operation, with the potential to generate energy savings. However, such advantage can only be exploited if the upstream process train is run at lower pressure, avoiding high-pressure units in the syngas gas conditioning section.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…On the downside, the use of MMC often entails a higher complexity derived from the microbial interactions between different trophic groups involved in the process, ultimately resulting in a poor understanding and limited process control. For instance, both mesophilic and thermophilic continuous syngas biomethanation processes have been previously reported to have a rather low product selectivity towards CH4, presenting a significant amount of unconverted fatty acids in the fermentation broth [16,17]. Thus, gaining better understanding on the activity of MMC is fundamental for the further development of the mixed culture-based syngas biomethanation process.…”
Section: Introductionmentioning
confidence: 99%